Determinants Maqashid Syariah Performance: Analysis of The Role of Islamic Social Reporting, Company Size, and Company Age of Islamic Banking in Indonesia and Malaysia - Rizfa Nurul Hanif; Muhammad Muflih (Jurnal Riset Akuntansi dan Keuangan, 2023)
The measurement of Islamic banking financial performance has only been measured according to business parameters to date. This study renews this view so that the view on Islamic banking is more comprehensive and fair. Good performance can provide opportunities for Islamic banks to continue to grow and be sustainable. The purpose of this study is to evaluate the role of Islamic Social Reporting (ISR), company size, and company age in influencing the performance of maqashid sharia Islamic banking in Indonesia and Malaysia for the period 2016-2021. With the quantitative method of panel data regression, simultaneously ISR, company size, and company age have a significant effect on the performance of maqashid sharia. Partially, the only company size has a significant effect, while ISR and company age do not. This study motivates Islamic banks to be consistent in developing ISR, company size, and company age in every aspect of bank operations.